2018
DOI: 10.1667/rr15148.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High- and Low-LET Radiation on Human Hematopoietic System Reconstituted in Immunodeficient Mice

Abstract: Over the last 50 years, a number of important physiological changes in humans who have traveled on spaceflights have been catalogued. Of major concern are the short-and long-term radiationinduced injuries to the hematopoietic system that may be induced by high-energy galactic cosmic rays encountered on interplanetary space missions. To collect data on the effects of space radiation on the human hematopoietic system in vivo, we used a humanized mouse model. In this study, we irradiated humanized mice with 0.4 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…The hematopoietic system of the human body that is sensitive to ionizing radiation has been evaluated in many studies [ 10 , 20 , 21 ]. According to reports, ionizing radiation exposure causes biological effects on human health including hematological parameters that change sooner or later, and hematopoietic syndrome is observed in animals and humans after systemic radiation exposure [ 22 ], including myelodysplastic disease by platelet elevation causing and chronic myelogenous leukemia [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hematopoietic system of the human body that is sensitive to ionizing radiation has been evaluated in many studies [ 10 , 20 , 21 ]. According to reports, ionizing radiation exposure causes biological effects on human health including hematological parameters that change sooner or later, and hematopoietic syndrome is observed in animals and humans after systemic radiation exposure [ 22 ], including myelodysplastic disease by platelet elevation causing and chronic myelogenous leukemia [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings provide a reasonably consistent picture of changing into hematological parameters associated with exposure to radiation. Moreover, there is a supplement to the risk assessment of low-dose ionizing radiation based on animal models [ 20 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although secondary immune organs are impacted by radiation, it remains to be investigated if there is a persistent shift in cell populations within this tissue at a longer time point after the exposure and how this could impact the adaptive response. Some studies have shown that both B-cells and T-cells are impacted by radiation in the spleen [ 25 , 60 ], including in humanized mice [ 61 ]. However, long-term responses to 28 Si irradiations did not reveal any differences in the population of humanized cells, compared to controls [ 61 ], or significant changes in the B- and T-cell populations in the spleen of mice [ 60 ] with 56 Fe.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that both B-cells and T-cells are impacted by radiation in the spleen [ 25 , 60 ], including in humanized mice [ 61 ]. However, long-term responses to 28 Si irradiations did not reveal any differences in the population of humanized cells, compared to controls [ 61 ], or significant changes in the B- and T-cell populations in the spleen of mice [ 60 ] with 56 Fe. However, Gridley et al did conclude that the more complex space radiation environment may lead to a broader immune dysfunction [ 60 ].…”
Section: Discussionmentioning
confidence: 99%